2004
DOI: 10.1128/aem.70.7.4371-4374.2004
|View full text |Cite
|
Sign up to set email alerts
|

Combined Immunomagnetic Separation-Molecular Beacon-Reverse Transcription-PCR Assay for Detection of Hepatitis A Virus from Environmental Samples

Abstract: In this study, a molecular-beacon-based real-time reverse transcription (RT)-PCR assay was developed to detect the presence of hepatitis A virus (HAV) in environmental samples. A 125-bp, highly conserved 5 noncoding region of HAV was targeted. The sensitivity of the real-time RT-PCR assay was tested with 10-fold dilutions of viral RNA, and a detection limit of 1 PFU was obtained. The specificity of the assay was demonstrated by testing with other environmental pathogens and indicator microorganisms, and only H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 19 publications
0
21
1
Order By: Relevance
“…Small amplicons are recommended, and this may also play a role in the speed; however, it has been shown that decreasing the size of the PCR fragment does not necessarily improve PCR performance (174). Molecular beacons (1,155,240) and TaqManbased assays (53) are a few of the chemistries that have been used for real-time PCR detection of HAV. Real-time PCR chemistries use primers and probes with separate fluorogenic labels; the generation of a fluorescent signal depends on the interaction between PCR products and/or probes (24,53,155,240).…”
Section: Molecular Detection Methodsmentioning
confidence: 99%
“…Small amplicons are recommended, and this may also play a role in the speed; however, it has been shown that decreasing the size of the PCR fragment does not necessarily improve PCR performance (174). Molecular beacons (1,155,240) and TaqManbased assays (53) are a few of the chemistries that have been used for real-time PCR detection of HAV. Real-time PCR chemistries use primers and probes with separate fluorogenic labels; the generation of a fluorescent signal depends on the interaction between PCR products and/or probes (24,53,155,240).…”
Section: Molecular Detection Methodsmentioning
confidence: 99%
“…from various foods (5,16,23). Antibodies specific for a particular microorganism are used, which gives the assay a higher specificity for concentrating and purifying microorganisms in both food and other environmental samples (1,6). The aim of this study was to evaluate IMS combined with real-time TaqMan RT-PCR for rapid and quantitative detection of NoV from artificially contaminated strawberries (11,20).…”
mentioning
confidence: 99%
“…A molecular beacon (HAV MB: 6-FAM-5Ј-CTTGCGGGATAGGGTAAC AGCGGCGGCGCAAG-3Ј-DABCYL [the stem sequence of the MB is underlined, and the target sequence of HAV is in bold]) (Midland Certified Reagent Co., Midland, TX), which is perfectly complementary to a 20-bp region of the amplicon, was designed based on aligning the sequences of 15 different HAV strains obtained from GenBank as described previously (1). The molecular beacon was labeled at the 5Ј-end with the fluorophore FAM (6-carboxyfluorescein), and DABCYL [4-(4Ј-dimethylaminophenylazo) benzoic acid] was used as the quencher at the 3Ј end.…”
Section: Methodsmentioning
confidence: 99%